Wealth inequalities in nutritional status among the tribal under-5 children in India: A temporal trend analysis using NFHS data of Jharkhand and Odisha states - 2006-21 - S. Rekha; P. Shirisha; V.R. Muraleedharan; Girija Vaidyanathan; Umakant Dash (Elsevier, 2023)
Background: Undernutrition remains a major public health concern in India, especially among children belonging to the Scheduled Tribes (ST). In this study, we analyse wealth inequalities in nutritional outcomes within ST communities in two tribal-dominated states of India, namely, Odisha and Jharkhand. The study also compares the trends in nutrition outcomes between ST and Non-ST children in these states. Methods: We have conducted a trend analysis of the prevalence and inequalities in the nutritional indicators among ST children under age five using unit-level data of the National Family Health Survey (NFHS) [NFHS-3(2005-06),4 (2015-16) and 5(2019-2021)]. Wealth-related inequalities were analysed using the Slope Index of Inequality (SII), which measures absolute inequality, and the relative Concentration Index (CIX), which measures relative inequality. We have also analysed the correlation between Antenatal Care (ANC) visits and nutritional indicators using the Pearson Correlation test. Results: The trend analysis shows that the prevalence of undernutrition remains higher among ST children in India as compared to Non-ST children between NFHS-3 (2005-06) and NFHS-5 (2019-2020) in Jharkhand and Odisha. The SII and CIX values show that statistically significant inequalities in stunting and underweight exist among children belonging to various wealth quintiles within the ST category in both states. Wasting is found to be significantly prevalent across all wealth quintiles. Also, we found a negative association between ANC visits and all three nutritional indicators. Interpretation: Our study highlights the importance of monitoring both the absolute and relative wealth inequalities in nutritional outcomes. This is due to the fact that while inequalities across groups may reduce, the prevalence of poor nutritional outcomes may increase among certain groups. Such observations, therefore, will enable policymakers to focus further on those groups and devise appropriate interventions.